The alterations of circulating mucosal-associated invariant T cells in polycystic ovary syndrome - Zhou, Hong; Xu, Junting; Hong, Ling; Jia, Yanping; Burk, Lilo Valerie; Chi, Fengli; Zhao, Mei; Guan, Xiaohong; Liu, Dan; Yin, Xiangjie; Zhang, Yiqiao; Teng, Xiaoming; et al. (Frontiers in Endocrinology, 2022)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder affecting reproductive age females and an important cause of infertility. Although the etiology is complex and its pathogenesis remains unclear, the pathological process of polycystic ovary syndrome (PCOS) is tightly related with the immune dysfunction and gut microbial dysbiosis. Mucosal-associated invariant T (MAIT) cells are a subset of innate-like T cells which can regulate inflammation through the production of cytokines and play a role in regulating the gut microbiota. We aim to evaluate the correlation between characteristics of PCOS and MAIT cells as well as their impact on cytokine secretion. Methods: Peripheral blood samples were taken from PCOS patients (n=33) and healthy controls (n=30) during 2-5 days of the menstrual period. The frequencies of MAIT cells and T cells were measured by flow cytometry. Cytokines interleukin 17 (IL-17), interleukin 22(IL-22), interferon γ (IFN-γ) and granzyme B were determined by Enzyme-linked immunosorbent assay (ELISA). Results: The frequency of MAIT cells was significantly reduced in the blood of PCOS patients compared with the controls. The frequency of MAIT cells was negatively correlated with Body Mass Index (BMI), Homeostatic model assessment- insulin resistance (HOMA-IR) index, and Anti Miillerian Hormone (AMH). Thus, the frequencies of MAIT cells decreased in PCOS patients with abnormal weight (BMI≥24kg/m2), higher HOMA-IR (≥1.5), and excessive AMH (≥8ng/ml). The Cytokine IL-17 was significantly higher in PCOS patients and negatively correlated with the frequency of MAIT cells. Even though the IL-22 was lower in PCOS Patients, no correlation with MAIT cells was detected. In subgroup, CD4+MAIT cells correlated with BMI, AMH, and testosterone (T) levels. Conclusion: The frequency change of MAIT cells may play a significant role in the pathogenesis of PCOS. Exploring these interactions with MAIT cells may provide a new target for PCOS treatment and prevention.